Tindak Pidana Plagiarisme Terhadap Desain Produk Ditinjau Dari Aspek Hak Asasi Manusia - Fajrina, Rahma Melisha; Malik, Kendall; Heruningrum, Heruningrum (INSTITUT SENI INDONESIA PADANGPANJANG, 2023)
Abstract This research is a normative legal research that aims to analyze the relationship between the criminal act of plagiarism and product design in terms of human rights aspects. The results of this study are that the crime of plagiarism against product design is an act that is contrary to Law number 39 of 1999 concerning human rights. The act of appropriating a design by another person without the owner's permission is an act of usurping the right to human welfare. Therefore, this research was carried out so that product designers realize that plagiarism on the designs they produce is a deprivation of the right to welfare that they must have.Keywords: Plagiarism, product design, human rights